Comparison of Electricity Usage Forecasting Model Evaluation Based on Historical Load Dataset Duration Using Long Short-Term Memory Architecture - Salleh N.S.M.; Suliman A.; Jrgensen B.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Brain; Electric power utilization; Electric utilities; Forecasting; Learning algorithms; Mean square error; Memory architecture; Electric power company; Electrical power; Electricity usage; Error values; Forecasting models; Load data; Mean absolute error; Mean squared error; Model evaluation; Primary sources; Long short-term memory